Meatballs with 3% and 6% dietary fibre from rye bran or pea fibre ‐ Effects on sensory quality and subjective appetite sensations. (March 2017) - Kehlet, Ursula; Pagter, Mette; Aaslyng, Margit D.; Raben, Anne
Abstract: This study investigated dose-response effects of rye bran and pea fibre added to meatballs on sensory quality and subjective appetite sensations. Pea fibre or rye bran was added to meatballs in doses ranging from 3 g to 6 g dietary fibre per 100 g. In a sensory profile, a trained panel ( n  = 9) evaluated the meatballs in terms of odour, appearance, texture and flavour attributes. In a cross-over appetite study, 27 healthy men were served five test meals. Subjective appetite sensations were assessed over a 4-hour period. The addition of rye bran to the meatballs increased the grainy odour, texture and flavour. Pea fibre resulted in a more crumbly, firm and gritty texture with increasing doses of fibre. The sensory changes followed a dose-response relationship. Subjective appetite sensations were not affected by the addition of fibre. Graphical abstract: